Los delitos culturalmente motivados: ¿Tienen cabida en el derecho penal canónico? - Alonso García, Carlos Ramiro (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2021)
The coexistence of different ethnic groups under the same legal system creates important challenges for criminal law. This paper focuses on reflecting on how culturally motivated crimes challenge the incorporation of the role of the author’s culture into the judgement of criminal responsibility. The article presents cases that exemplify this problem, drawing out the concept of culturally motivated crime and lays down the requirements for trial testing. Finally, a dialog is established between secular and canonical criminal law — which is the main pretence of the work — that may lead to consider the opportunity and the way to apply this category in the law of the Church, which is the most universal and multicultural that exists considering of its beneficiaries. With this in mind, several possible solutions are analysed within the current canonical regulations.